Pulmonary Vascular Input Impedance is a Combined Measure of Pulmonary Vascular Resistance and Stiffness and Predicts Clinical Outcomes Better than PVR Alone in Pediatric Patients with Pulmonary Hypertension - Hunter, Kendall S. (2007)
BACKGROUND: Pulmonary vascular resistance (PVR) is the current standard for evaluating reactivity in children with pulmonary arterial hypertension (PAH). However, PVR measures only the mean component of right ventricular afterload and neglects pulsatile effects. We recently developed and validated an method to measure pulmonary vascular input impedance, which revealed excellent correlation between the zero-harmonic impedance value and PVR, and suggested a correlation between higher harmonic impedance values and pulmonary vascular stiffness (PVS). Here we show that input impedance can be measured routinely and easily in the catheterization laboratory, that impedance provides PVR and PVS from a single measurement, and that impedance is a better predictor of disease outcomes compared to PVR. METHODS: Pressure and velocity waveforms within the main PA were measured during right-heart catheterization of patients with normal PA hemodynamics (n=14) and those with PAH undergoing reactivity evaluation (49 subjects; 95 conditions). A correction factor needed to transform velocity into flow was obtained by calibrating against cardiac output. Input impedance was obtained off-line by dividing Fourier-transformed pressure and flow waveforms. RESULTS: Exceptional correlation was found between the indexed zero harmonic of impedance and indexed PVR (y=1.095·x+1.381, R(2)=0.9620). Additionally, the modulus sum of the first two harmonics of impedance was found to best correlate with indexed pulse pressure over stroke volume (PP/SV) (y=13.39·x-0.8058, R(2)=0.7962). Amongst a subset of PAH patients (n=25), cumulative logistic regression between outcomes to total indexed impedance was better (R(L)(2)=0.4012) than between outcomes and indexed PVR (R(L)(2)=0.3131). CONCLUSIONS: Input impedance can be consistently and easily obtained from PW Doppler and a single catheter pressure measurement, provides comprehensive characterization of the main components of RV afterload, and better predicts patient outcomes compared to PVR alone.